La inteligencia emocional en el desarrollo de la competencia de liderazgo en la empresa familiar Soluciones Empresariales HTS (2021)
The objective of this degree project is to identify the level of emotional intelligence of the company's leaders SOLUCIONES EMPRESARIALES HTS SAS, thus determining the main situations that may be affecting the company, conducting an intervention through a survey seeking the participation of all leaders , through which you can identify opportunities for improvement and thus be able to provide support and recommendations to improve your work activities and possible returns based on optimal emotional intelligence.